2012
DOI: 10.1071/ah11043
|View full text |Cite
|
Sign up to set email alerts
|

Workplace abuse among correctional health professionals in New South Wales, Australia

Abstract: Objective. Studies have found that health workers are at elevated risk of being abused while at work. Little is known, however, about workplace abuse among correctional health professionals. We implemented a cross-sectional study to investigate the prevalence, sources and consequences of workplace abuse among correctional health professionals in New South Wales, Australia.Methods. All employees of Justice Health (a statutory health corporation) were invited to complete a self-administered survey, which was del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
3
14
0
4
Order By: Relevance
“…Os autores da violência ocupacional incluem gerentes, colegas de trabalho -profissionais de saúde e de outras áreas -, pacientes e familiares. 4,5 Na área hospitalar, o risco de violência ocupacional é maior entre os profissionais de enfermagem dos serviços de urgência e emergência, [6][7][8][9] visto que eles integram a linha de frente e são responsáveis pelo cuidado em tempo integral. Por conseguinte, são os primeiros a receberem manifestos de insatisfação com o serviço.…”
Section: Introductionunclassified
“…Os autores da violência ocupacional incluem gerentes, colegas de trabalho -profissionais de saúde e de outras áreas -, pacientes e familiares. 4,5 Na área hospitalar, o risco de violência ocupacional é maior entre os profissionais de enfermagem dos serviços de urgência e emergência, [6][7][8][9] visto que eles integram a linha de frente e são responsáveis pelo cuidado em tempo integral. Por conseguinte, são os primeiros a receberem manifestos de insatisfação com o serviço.…”
Section: Introductionunclassified
“…Examples of mental health problems that can develop in the victims of workplace violence include anxiety, stress, a feeling of helplessness and, in rare cases, suicidal ideation [14,16-20]. Although its impact on patient care has not been directly measured, a number of self-report studies have found that violence in health care settings likely undermines the quality of health services provision [11,16,17,20-23] – by contributing to clinical errors, for example [11,23]. Clinical errors can happen when a victim of workplace violence (a health professional) worries excessively and/or experiences difficulty concentrating as a result of the incident(s) [11,23].…”
Section: Introductionmentioning
confidence: 99%
“…Although its impact on patient care has not been directly measured, a number of self-report studies have found that violence in health care settings likely undermines the quality of health services provision [11,16,17,20-23] – by contributing to clinical errors, for example [11,23]. Clinical errors can happen when a victim of workplace violence (a health professional) worries excessively and/or experiences difficulty concentrating as a result of the incident(s) [11,23]. Further, the perception of an unsafe workplace has been found to lower staff morale and lead to increased staff attrition [11,14,21,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations